The Role Of Law In Maintaining Social Justice In Indonesia Through Community Training And Empowerment - Madinah Mokobombang; Nenden Herawaty Suleman; Sabil Mokodenseho; Kirana Putri Calya; Meisi Mamonto; Muhammad Julianto Sumanta (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the role of law in maintaining social justice in Indonesia through community training and empowerment as an effort to strengthen legal literacy and access to justice. Using qualitative methods with a descriptive-analytical approach, this study explores the experiences, perceptions, and practices of communities involved in legal training programs organized by local governments, non-governmental organizations, and local communities. Data were collected through in-depth interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that legal training contributes significantly to increasing understanding of basic rights, increasing community courage in accessing legal services, and establishing community paralegals capable of assisting citizens in resolving simple legal issues. Multi-stakeholder collaboration and the use of technology have also expanded the reach of legal education to communities in various regions. However, structural barriers such as complex bureaucracy and limited facilities remain challenges in achieving equitable social justice. Overall, this study confirms that community training and empowerment are effective strategies for strengthening the function of law as a guardian of inclusive and sustainable social justice.